The Effect of Different Levels of CLA and Omega-3 Supplements Along with Essential Oils of Fennel, Peppermint, and Eucalyptus Medicinal Plants on Production Performance, Blood Parameters, and Reproductive Performance Activity in Laying Hens of the Lehman Breed - Yadollah Chashnidel; Matin Movagharnezhad; Mehdi Jafary charati (پژوهشهای تولیدات دامی)
Extended Abstract Background: Fats and fatty acids in the poultry diet have major physiological roles. A good source of oil or fat should have an ideal ratio of saturated and unsaturated fatty acids. The increase in the consumption of fat sources increases the possibility of oxidative corruption, which is very dangerous. It is better to use sources containing antioxidant compounds along with sources containing fatty acids to reduce the occurrence of these risks. Medicinal plants have antioxidant properties that play an essential role in improving the immune system and preventing various infections. The ability of a mixture of medicinal plants to show their beneficial biological effects is much stronger than the individual effect. This study investigated the effect of different levels of conjugated linoleic acid and omega-3 supplements along with the essential oils of medicinal plants, such as fennel powder, peppermint, and eucalyptus, on production performance, blood parameters, and reproductive performance activity in laying hens of the Lehman breed. Methods: This experiment was conducted on 60 chickens with an average weight of 1.5±0.2 and an age of 34 weeks in four treatments with five replications and three chickens in each replication in a completely randomized design for 42 days. The experimental diets included a control treatment (without additives) and treatments containing 0.25, 0.375, and 0.5% CLA and omega-3 enriched with medicinal plants at three levels (0.25, 0.375, and 0.5%) in the diets. A separate cage was considered for every three chickens for one week before the start of the experiment. Habituation to the ration and uniformity of the weight of the chickens was done in the cage. During the experimental period, the chickens had full access to water freely. Functional traits of the egg production rate and the average weight of eggs were measured daily, and feed consumption and conversion factor were measured weekly. At the end of the test period, two pieces of eggs were randomly selected from each replication and weighed with a digital scale with an accuracy of 0.001 g. Then, the eggs were broken to measure the Haugh unit, yolk color, and quality characteristics of the shell. To measure blood parameters at the end of the experiment (day 42), blood samples were collected from the wing vein of two laying hens per experimental unit and analyzed in the laboratory for glucose, triglyceride, cholesterol, total protein, and uric acid levels. Additionally, the liver fat profile and amount were measured by selecting two chickens from each group at the end of the study and examining their livers post-slaughter. Reproductive characteristics were also investigated by randomly selecting two chickens from each treatment and evaluating the contents of their abdominal cavity, including the ovary, oviduct, stroma, and follicles. Results: The results of production performance showed that the high level of supplementation (1%) caused better production performance than the other levels and the control treatment (p < 0.05). The results of the produced egg weight also showed a statistically significant difference between all levels of the conjugated linoleic acid supplement with omega-3 and the mixture of medicinal plants used in the control treatment (p < 0.05). In the results of shell thickness, there were no significant differences between experimental treatments (p > 0.05). The results of blood serum parameters at the end of the test period showed a significant difference in the blood serum lipid parameters between the experimental treatments (p < 0.05). The lowest amount of cholesterol was observed in the treatment containing 1% conjugated linoleic acid supplement along with omega-3 and a mixture of medicinal plants. With the increase of the supplement level in the experimental diets, a significant decrease was observed in other blood serum parameters, except for VLDL and HDL. The results of ovarian follicle activity showed that the highest ovarian function belonged to treatments 2 and 3 (p < 0.05). The best results of evaluating the appearance of the liver and the amount of total liver fat were obtained in treatments 2 and 3 (p < 0.05). The overall results showed that the high level of CLA and Omega-3 supplements together with medicinal plants could improve the functional traits of laying hens of the Lehman breed. In the activity of ovarian follicles, an increase in the activity of follicles was observed with an increase in the supplement level in the diet compared to the control treatment. Conclusion: In general, the results showed that the use of supplements not only does not have a negative effect but positive results are obtained in production performance, blood parameters, liver characteristics, and reproductive performance activity in laying hens of the Lohman breed, especially at the high level.